1971
DOI: 10.1113/jphysiol.1971.sp009535
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the reflex response to stimulation of carotid sinus baroreceptors during and following stimulation of the hypothalamic defence area in the cat

Abstract: 3. During hypothalamic stimulation the reflex fall in blood pressure resulting from a rise in sinus pressure was found to be undiminished whether sinus pressure was raised at the onset or at the 10th sec of hypothalamic stimulation.4. By contrast, in at least half the cats in which a reflex bradyeardia could be evoked from the sinus, this bradycardia was largely if not completely suppressed during hypothalamic stimulation. This suppression of reflex bradycardia occurred when sinus pressure was raised at the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

1972
1972
2002
2002

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 14 publications
1
15
1
Order By: Relevance
“…This interaction between the primary cardiovascular response to cerebral ischemia and baroreceptor reflexes contrasts with that occurring in another centrally organized cardiovascular response, the defense reaction (Djojosugito et al, 1970;Gebber and Snyder, 1970;Humphreys et al, 1971) in which the cardiac component of the baroreceptor reflex is suppressed. These observations reinforce the view that the cardiac and vasomotor components of the baroreceptor reflex can be dissociated, and each separately controlled by other regions of the brain (Djojosugito et aL, 1970;Gebber and Synder, 1970;Humphreys et aL, 1971).…”
Section: Minutementioning
confidence: 76%
“…This interaction between the primary cardiovascular response to cerebral ischemia and baroreceptor reflexes contrasts with that occurring in another centrally organized cardiovascular response, the defense reaction (Djojosugito et al, 1970;Gebber and Snyder, 1970;Humphreys et al, 1971) in which the cardiac component of the baroreceptor reflex is suppressed. These observations reinforce the view that the cardiac and vasomotor components of the baroreceptor reflex can be dissociated, and each separately controlled by other regions of the brain (Djojosugito et aL, 1970;Gebber and Synder, 1970;Humphreys et aL, 1971).…”
Section: Minutementioning
confidence: 76%
“…Electrical stimulation of the carotid sinus nerve, which activates both receptor pathways, produces the same result. Stimulation of a particular area in the hypothalamus, usually called the defence area, has been repeatedly shown to inhibit the bradycardia produced by baroreceptor stimulation [Hilton, 1963;Humphreys, Joels and McAllen, 1971], by chemoreceptor stimulation [Thomas and Calaresu, 1973] or by sinus nerve stimulation [Hilton, 1963;Gebber and Snyder, 1970].…”
Section: (Receivedforpublication 26th May 1977) (Revised Version 23rdmentioning
confidence: 99%
“…59 P. W. HUMPHREYS AND N. JOELS Stimulion of the hypothclamus. Identification and stimulation of the defence area was carried out as described by Humphreys et al (1971). The stimulating electrode was a ground and electrolytically thinned stainless-steel needle insulated with Araldite 985E (C.I.B.A.)…”
Section: Methodsmentioning
confidence: 99%
“…During such stimulation the bradycardia normally induced by a rise in carotid sinus pressure is suppressed (Hilton, 1963(Hilton, , 1965Djojosugito, Folkow, Kylstra, Lisander & Tuttle, 1970;Gebber & Snyder, 1970;Humphreys, Joels & McAllen, 1971), but there is less unanimity about the response of the blood pressure. Hilton (1963Hilton ( , 1965 claimed that the reflex fall in pressure also was suppressed, Djojosugito et al (1970) observed suppression only at high intensities of hypothalamic stimulation, while Gebber & Snyder (1970) and Humphreys et al (1971) found that the fall in pressure was unaltered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation